2021
DOI: 10.3389/fpsyt.2021.575553
|View full text |Cite
|
Sign up to set email alerts
|

Mental Distress and Its Contributing Factors Among Young People During the First Wave of COVID-19: A Belgian Survey Study

Abstract: Background: The outbreak of the COVID-19 pandemic in 2020 and its associated measures led to high levels of mental distress in the general population. Previous research indicated that young people are especially vulnerable for a wide range of mental health problems during the pandemic, but little is known about the mechanisms. This study examined mental distress and its contributing factors among young Belgian people.Methods: An online survey was widely distributed in Belgium during the first wave of COVID-19 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
64
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(81 citation statements)
references
References 47 publications
9
64
1
2
Order By: Relevance
“…Moreover, the significance of resilience might also reflect more external than internal resilience factors, as this measure included many items on social support, and as the correlation with our social support measure was quite high (i.e., 0.70; see Appendix 6). Therefore, despite the non-significance of the association between social support and psychopathology, strong social networks are still likely important factors in safeguarding adolescents' mental health during the pandemic -in line with previous work evidencing this link (Dvorsky et al, 2021;Nitschke et al, 2021;Rens et al, 2021;Veer et al, 2021).…”
Section: Associated With Psychopathology Symptomssupporting
confidence: 77%
“…Moreover, the significance of resilience might also reflect more external than internal resilience factors, as this measure included many items on social support, and as the correlation with our social support measure was quite high (i.e., 0.70; see Appendix 6). Therefore, despite the non-significance of the association between social support and psychopathology, strong social networks are still likely important factors in safeguarding adolescents' mental health during the pandemic -in line with previous work evidencing this link (Dvorsky et al, 2021;Nitschke et al, 2021;Rens et al, 2021;Veer et al, 2021).…”
Section: Associated With Psychopathology Symptomssupporting
confidence: 77%
“…Belgian respondents reported the highest new incidence of anxiety, depression, and PTSD across all countries studied, and the highest prevalence of anxiety (presumed diagnosis based on positive screening results). We did not investigate the effect of loneliness and low social support on mental health, but a study among young Belgium people found these factors to be the main predictors of mental distress [49]. Another study in Belgium found psychological distress to be associated with the consequences of the Covid-19 pandemic and containment measures [50].…”
Section: Discussionmentioning
confidence: 97%
“…The anxiety subscale consists of items 2, 4, 7, 9, 15, 19, and 20, with scores ranging from normal (0-7), mild (8)(9), moderate (10)(11)(12)(13)(14), severe (15)(16)(17)(18)(19), to extremely severe (20+). Finally, the stress subscale consists of items 1, 6, 8, 11, 12, 14, and 18, with scores ranging from normal (0-14), mild (15)(16)(17)(18), moderate (19)(20)(21)(22)(23)(24)(25), severe (26)(27)(28)(29)(30)(31)(32)(33), to extremely severe (34+). The DASS-21 is a reliable, easy-to-use screening instrument and has been wellreceived globally.…”
Section: Depression Anxiety and Stress Scalesmentioning
confidence: 99%
“…We used the English version of the UCLA-LS scale validated by past research (28). Participants with a score of 6 or higher were categorized as experiencing a high level of loneliness (29). The score then collapsed into one of two categories: a score of 3-5 reflects a negative screening for loneliness, and a score of 6-9 reflects a positive screening for loneliness.…”
Section: University Of California Los Angeles Loneliness Scalementioning
confidence: 99%